British Journal of Sports Medicine in the digital age - Michell, D. (British Journal of Sports Medicine, 2006)
Up to date ways of accessing information using BJSM are outlined. As the nature of publishing has shifted in a digital age, so the role of a publisher has changed from guardian to gateway, and so our websites need to facilitate finding content quickly and efficiently. Several new online features make British Journal of Sports Medicine (BJSM) work for you. With greater interaction you can get maximum use with minimal effort.